Teachers’ Opinion Concerning the Current Translation Courses at Undergraduate Departments of English in Kurdistan Region-Iraq (Journal of the College of Basic Education, 2019)
This study represents the views of a range of translation teachers concerning the translation courses offered at Departments of English, College of Languages in Kurdistan Region, Iraq. It aims at drawing a clear image of these courses from the teachers’ points of view and exploring the difficulties they have encountered in teaching these courses. To achieve the aim of this study, the researcher interviewed eighteen teachers who have experience in teaching translation at Departments of English, ( 7) from Salahaddin University- Erbil, (4) from University of Sulaimani, and (7) from University of Duhok. Three main questions have been raised by the researcher to elicit teachers’ opinions and find to which extent they were satisfied with teaching these courses. Accordingly, it has been found out that teachers of translation are satisfied with the translation courses to some extent, but there are some drawbacks which needed to be addressed and overcome to increase the effectiveness of the teaching and learning process in the courses understudy. So, in the light of the current drawbacks, setting clear objectives/ learning outcomes and aligning them with all the other translation courses’ components are required.